2020
DOI: 10.1017/s0963548320000127
|View full text |Cite
|
Sign up to set email alerts
|

Finding independent transversals efficiently

Abstract: We give an efficient algorithm that, given a graph G and a partition V1,…,V m of its vertex set, finds either an independent transversal (an independent set {v1,…,v m } in G such that ${v_i} \in {V_i}$ for each i), or a subset ${\cal B}$ of vertex classes such that the subgraph of G induced by $\bigcup\nolimits_{\cal B}$ has a small dominating set. A non-algorithmic proof of this result has been known f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Aharoni et al [1] showed that when b ≥ 2Δ, there exists an IT I with w(I) ≥ w(V)∕b. The work [10], building on [9], gives a nearly-matching randomized algorithm under the condition b ≥ (2 + 𝜀)Δ for constant 𝜀 > 0. Similarly, when w(v) ≥ 0 for all v (we say in this case that w is non-negative) and b ≥ 4Δ, then [19] shows that the randomized MT algorithm directly gives an IT I with w(I) ≥ Ω(w(V)∕b).…”
Section: Independent Transversalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aharoni et al [1] showed that when b ≥ 2Δ, there exists an IT I with w(I) ≥ w(V)∕b. The work [10], building on [9], gives a nearly-matching randomized algorithm under the condition b ≥ (2 + 𝜀)Δ for constant 𝜀 > 0. Similarly, when w(v) ≥ 0 for all v (we say in this case that w is non-negative) and b ≥ 4Δ, then [19] shows that the randomized MT algorithm directly gives an IT I with w(I) ≥ Ω(w(V)∕b).…”
Section: Independent Transversalsmentioning
confidence: 99%
“…Many combinatorial problems, such as graph list‐coloring, can be formulated in terms of independent transversals; see [8] for a more extensive background. One fundamental problem is to determine sufficient conditions for the existence of an independent transversal in a graph.…”
Section: Independent Transversalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many combinatorial problems can be formulated in terms of independent transversals, such as satisfiability and graph list-coloring. See [12] for a more extensive background.…”
Section: Independent Transversalsmentioning
confidence: 99%
“…When no special information is known about the structure of the graph with respect to the vertex partition, the combinatorial and topological methods appear to work best, giving the best possible results in many cases. One example is the following [14,15], where a partition  is said to be t-thick if each of its blocks has size at least t, and as usual G Δ( ) denotes the maximum degree of G. (This is one of the most frequently applied IT theorems, see, e.g., [12] and the references therein.) Theorem 1 (Haxell [14,15]).…”
mentioning
confidence: 99%